Penyusunan Penjadwalan Produksi pada CV. Syam’s Indonesia Handicraft Menggunakan Metode Campbell Dudek Smith (CDS) Guna Meminimasi Nilai Makespan - Aulia Fajrin, Nazilatul; Budi Utomo, Sukarno; Ernawati, Rieska (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
CV. Syam's Handicraft Indonesia is a company engaged in fashion, by producing woven bags made from processed waste materials. The production system used in this company uses a make-to-order system with a flow shop pattern or has the same production stages. This company applies the First Come First Serve (FCFS) scheduling system where orders that enter first will be prioritized for processing. As a result of the application of this method, several times the company experienced delays in shipping goods, causing protests from customers. Based on these problems, a calculation method is needed to arrange production scheduling with the aim of determining and producing effective and optimal scheduling. In this study, the method used for calculation and as a comparison is the Campbell Dudek Smith (CDS) method. The results of the calculation using the Campbell Dudek Smith (CDS) method obtained the priority order of work A-C-G-B-D-F-E with a makespan of 3,146.42 minutes with a flowtime of 79,582.68 minutes. While the calculation results with the First Come First Serve (FCFS) method, which is the method applied to the company with the priority order of work A-B-C-D-E-F-G, resulted in a makespan of 3159.91 minutes and a flowtime of 81,873.50 minutes. It can be concluded that the proposed method, namely Campbell Dudek Smith (CDS), produces a smaller makespan value with a difference in makespan value of 13.49 minutes or with a percentage difference in RE of 0.42% and IE of 1.04 the proposed method, Campbell Dudek Smith (CDS) can produce more effective scheduling.